Perubahan Bahasa Aceh: Tinjauan Realitas Penggunaan Bahasa Aceh dalam Interaksi Sosial di Aceh - Teuku Alamsyah; Muhammad Iqbal; Rostina Taib (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This study aimed to describe changes the Acehnese language in the lexical aspect in the reality of everyday Acehnese speech. Qualitative research methods have also been established as research methods for all research activities. Two groups of bilingual speakers, namely the Acehnese (Aceh-Indonesian) ethnic community who speak two languages, namely Acehnese and Indonesian in daily social interactions and the bilingual Acehnese (Aceh-Indonesian) ethnic community who use the Acehnese language in social interactions have been designated as data source. The study was carried out in three districts/cities in Aceh Province, namely Banda Aceh City, Aceh Besar District, and Aceh Jaya District, involving participants in childhood, adulthood, and old age. The results showed that the lexical changes of language were in the form of lexical loss, lexical borrowing, and lexical creation. The most dominant factor causing the Acehnese lexical change is the external motivation factor. The conclusion of this study is that the lexical change of the Acehnese language in the context of bilingual speakers has taken place, is ongoing, and has the potential to continue in line with the social changes of society due to the progress of the times. AbstrakPenelitian ini bertujuan mendeskripsikan perubahan bahasa Aceh pada aspek leksikal dalam realitas tuturan penutur bahasa Aceh sehari-hari. Metode penelitian kualitatif pula telah ditetapkan sebagai metode penelitian untuk keseluruhan aktivitas penelitian. Dua kelompok penutur bilingual, yaitu masyarakat etnis Aceh (Aceh-Indonesia) penutur dua bahasa, yaitu bahasa Aceh dan bahasa Indonesia dalam interaksi sosial sehari-hari dan masyarakat etnis Aceh bilingual (Aceh-Indonesia) yang menggunakan bahasa Aceh dalam interaksi sosial telah ditetapkan sebagai sumber data. Kajian dijalankan pada tiga kabupaten/kota di Provinsi Aceh, yaitu Kota Banda Aceh, Kabupaten Aceh Besar, dan Kabupaten Aceh Jaya dengan melibatkan partisipan usia kanak-kanak, usia dewasa, dan usia tua. Hasil penelitian menunjukkan bahwa perubahan leksikal bahasa wujud dalam bentuk kehilangan leksikal, peminjaman leksikal, dan penciptaan leksikal. Faktor penyebab perubahan leksikal bahasa Aceh yang paling dominan adalah faktor motivasi eksternal. Simpulan hasil kajian ini adalah perubahan leksikal bahasa Aceh dalam konteks penutur bilingual telah berlangsung, sedang berlangsung, dan memiliki potensi akan terus berlangsung sejalan dengan perubahan sosial masyarakat akibat kemajuan zaman.